Efektivitas Media Audio Visual Terhadap Pengetahuan Ibu tentang Gizi Balita di Desa Penyaguan Kabupaten Indragiri Hulu - Hayati, Nurtipa; Lisviarose, Lisviarose (Pustaka Galeri Mandiri, 2025)
The First 1000 Days of Life constitutes a critical window for optimal child growth and development, during which nutritional deficiencies may result in long-term consequences such as stunting and cognitive impairment. Globally, 22% of children under five are stunted and 7.5% experience wasting, while in Indonesia, the prevalence of undernutrition reached 17.1% and wasting increased to 7.7% in 2022. One of the primary determinants of child nutritional status is maternal nutrition knowledge, which remains insufficient in many communities. Audio-visual media has been recognized as an effective tool to enhance maternal understanding and support appropriate nutritional practices for young children. This study aimed to assess the effectiveness of audio-visual media in improving maternal knowledge regarding toddler nutrition in Penyaguan Village, Indragiri Hulu Regency, in 2025. A pre-experimental one-group pretest-posttest design was employed, involving 39 mothers of toddlers selected through total sampling. Maternal knowledge was measured using a structured questionnaire, and the intervention consisted of nutrition education delivered through audio-visual media. Data were analyzed using the paired sample t-test. Findings demonstrated an increase in mean knowledge scores from 10.33 prior to the intervention (range 7–18) to 13.26 following the intervention (range 9–17). Statistical testing yielded a p-value of 0.001 (<0.05), indicating a significant improvement in maternal knowledge after the intervention. In conclusion, audio-visual-based education effectively enhances maternal knowledge regarding toddler nutrition and may be recommended as a strategic educational approach to support early childhood nutrition programs. The findings of this study will be disseminated through publication in a nationally accredited scientific journal.